Environmental protection or economic growth? The effects of preferences for individual freedoms - Čábelková, Inna; Smutka, Luboš; Mareš, David; Ortikov, Akhmadjon; Kontsevaya, Stanislava (Frontiers in Environmental Science, 2023)
Environmental protection is often seen in conflict with individual freedom and economic growth. The proponents of environmental protection suggest that the environment is a global resource that must be protected for future generations, even at the expense of economic growth and individual freedoms. The opponents claim that environmental protection should not come at the expense of individual rights and liberties, economic growth included. This paper studies the associations between public preferences for environmental protection, economic growth, and individual freedoms in eleven post-soviet countries on a representative dataset (N=20006, age 18+, M ± SD: 46,04 ± 17,07; 58% women, 46,8% upper education). Methodologically we rely on correlations, principal component analysis, and ordinal regression analyses. The results suggest that preferences for most personal freedoms studied predict environmental protection and economic growth preferences. In addition, preferences for civil rights, rights for democracy, gender equality, income inequality, and the low role of the army in politics predicted higher preferences for environmental protection and economic growth. Interestingly, the government's right to video surveillance in public areas, though diminishing personal freedoms in terms of anonymity, predicted higher preferences for environmental protection and economic growth. The importance of God in lives proved to increase preferences for environmental protection but was negatively related to preferences for economic growth. We suggest the government communicate the need for environmental protection as a part of the rights for individual freedom to live in a clean environment.